2023
DOI: 10.3390/cimb45070351
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomic and Metabolomic Analyses Unveil the Protective Effect of Saffron in a Mouse Colitis Model

Abstract: Despite the existence of effective drugs used to treat inflammatory bowel disease (IBD), many patients fail to respond or lose response over time. Further, many drugs can carry serious adverse effects, including increased risk of infections and malignancies. Saffron (Crocus sativus) has been reported to have anti-inflammatory properties. Its protective role in IBD and how the microbiome and metabolome play a role has not been explored extensively. We aimed to establish whether saffron treatment modulates the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…We are currently conducting a clinical trial that stems from a successful in vitro and in vivo data extrapolation to humans with ulcerative colitis [ 12 , 17 ]. In this clinical trial, we used two saffron concentrations after extrapolating from mice findings to human body weight [ 13 ]. We are assessing the presence of saffron compounds in the plasma of the recruited patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are currently conducting a clinical trial that stems from a successful in vitro and in vivo data extrapolation to humans with ulcerative colitis [ 12 , 17 ]. In this clinical trial, we used two saffron concentrations after extrapolating from mice findings to human body weight [ 13 ]. We are assessing the presence of saffron compounds in the plasma of the recruited patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have reported the anti-inflammatory effects of saffron treatment in gastrointestinal disorders and saffron’s antitumor effects on gastric cancer, colorectal cancer, liver cancer, and pancreatic cancer [ 12 , 13 ]. In prostate cancer, preclinical studies of the oral treatment of saffron and its major metabolites crocetin (CCT) and crocin (CR) in aggressive-PCa-cell-line xenografts in male nude mice also showed antitumor effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a huge number of drugs being designed to treat numerous diseases, the adverse effects such as decreasing the beneficial gut microbiome, risk of infection, toxicity, and malignancies diminish their applicability in humans. Saffron and its derivative compounds are alternatives to eliminating the pro-inflammatory bacteria and regulating the beneficial microbes such as Firmicutes/Bacteroides in mouse models [ 173 ]. These studies also demonstrated the role of saffron in regulating microbiome-associated metabolites such as 2 hydroxyglutaric acid, cholesterol, uric acid, 2-hydroxyhexanoic acid, and allantoic acid.…”
Section: Regulation Of Gut Microbiome By Saffron and Its Metabolites:...mentioning
confidence: 99%
“…These studies also demonstrated the role of saffron in regulating microbiome-associated metabolites such as 2 hydroxyglutaric acid, cholesterol, uric acid, 2-hydroxyhexanoic acid, and allantoic acid. In conclusion, saffron plays a pivotal role in maintaining the homeostatic balance in regulating the gut microbiome and healthy state of the gut [ 173 ]. Recently, Pontifex et al [ 174 ] reported that the saffron extract reduces anxiety-related behavior in a rat model of low-grade inflammation via modulating the microbiota and gut metabolites.…”
Section: Regulation Of Gut Microbiome By Saffron and Its Metabolites:...mentioning
confidence: 99%